Evaluation of the State of the Ecologically Problematic Mining and Industrial Objects in Kalush Region by Electromagnetic Methods and their Monitoring - Deshchytsya, S.A.; Pidvirny, O.I.; Romanyuk, O.I.; Sadovy, Yu.V.; Kolyadenko, V.V.; Savkiv, L.G.; Myshchyshyn, Yu.S. (Science and Innovation, 2024)
Environmentally hazardous geological processes in the waste deposits of potash and rock salts pose significant threats to the environment. To detect, to study, and to prevent in time such the processes (karsting, suffosations, landslides) a hardware and software complex for induction sounding of the geological environment in the near zone of field source has been created and tested. The multiprocessor system for management, collection, and transfer of the data for analysis and operational geological interpretation to the end users has been developed.